Regulation of the Drosophila hypoxia-inducible factor alpha Sima by CRM1-dependent nuclear export - Romero, Nuria Magdalena (2008)
Hypoxia-inducible factor alpha (HIF-alpha) proteins are regulated by oxygen levels through several different mechanisms that include protein stability, transcriptional coactivator recruitment, and subcellular localization. It was previously reported that these transcription factors are mainly nuclear in hypoxia and cytoplasmic in normoxia, but so far the molecular basis of this regulation is unclear. We show here that the Drosophila melanogaster HIF-alpha protein Sima shuttles continuously between the nucleus and the cytoplasm. We identified the relevant nuclear localization signal and two functional nuclear export signals (NESs). These NESs are in the Sima basic helix-loop-helix (bHLH) domain and promote CRM1-dependent nuclear export. Site-directed mutagenesis of either NES provoked Sima nuclear retention and increased transcriptional activity, suggesting that nuclear export contributes to Sima regulation. The identified NESs are conserved and probably functional in the bHLH domains of several bHLH-PAS proteins. We propose that rapid nuclear export of Sima regulates the duration of cellular responses to hypoxia.